NILAI-NILAI PENDIDIKAN ISLAM DALAM TRADISI PERINGATAN TAHUN BARU HIJRIYAH - Bowo, Rudi Triyo (Prodi PGMI IAIN Salatiga, 2009)
The purpose of this study was to determine the history of the new year hijriyah implemented, the stage of the ritual and the perception of the community about the new year ritual hijriyah as well as to determine the values of Islamic education in the new year hijriyah in the TRAJI village, Parakan district, Kab. Temanggung. The research is conducted qualitatively. The research results showed that the originator of the new year hijriyah tradition held in the TRAJI village is mastermind Garu, the ritual is the preparation stage; done before the carnival, implementation; start of carnival and ritual ceremony performed in the spring Sidukun, cover; the whole ritual procession in covered with leather puppet performances. The perception of most people around to believe that by implementing the new year ritual in hijriyah will bring blessing and favor and if not held tradition else something bad will happen. Values of Islamic education in the tradition of the hijriyah new year in the TRAJI village is the educational value of history, the advice of kindness, unity and integrity as well as the educational value of local wisdom. The value of unity is very important given the villagers of TRAJI which consists of various religions and beliefs, it can be an example in inter-religious harmony in the life of the nation.